Implementation of Permendikbud No. 20 Article 8 Paragraph 4 of 2018 at SD Muhammadiyah 10 Balongbendo: Implementasi Permendikbud No. 20 Pasal 8 Ayat 4 Tahun 2018 Di SD Muhammadiyah 10 Balongbendo - Faisal Ali Burhanudin; Akhtim Wahyuni (Indonesian Journal of Education Methods Development, 2020)
This study aims to describe the Implementation of Permendikbud No. 20 Article 8 Paragraph 4 in 2018 at SD Muhammadiyah 10 Balengbendo. The type of research below is a qualitative descriptive study. The subject of the study were the elementary school teacher Muhammadiyah 10 Balongbendo. This research was conducted in April 2019. Data collection techniques used were observation, interviews and documentation. The technique of checking the validity of the data is the source triangulation.The results showed that the implementation of Permendikbud No. 20 Article 8 Paragraph 4 in 2018 at SD Muhammadiyah 10 Balengbendo related duties and responsibilities that act as Educator, protective, facilitators and catalysts are as follows: (1) its role as a connecting learning resources teachers have done their responsibilities in carrying out the learning process. (2) In their role as protectors of all teachers at SD Muhammadiyah 10 Balengbendo, they always provide supervision to all their students, which are carried out from the beginning to the end of coming home with the aim of filtering out positive or negative things that students will receive. (3) its role as facilitator the teacher always opens space for students to establish an intimacy so that they feel close to us. (4) its role as a teacher catalyst helps students explore and optimize the potential possessed by each students to be directed in all activities that exist in school and outside of school. “